Separation of Gold from Nickel, Cobalt and Zinc by a Poly(hydroxamic acid) Ion-exchange Resin - Wan Yunus, Wan Md Zin; Haron, Md Jelas; Tan, Lai Hong (Universiti Putra Malaysia Press, 1996)
Behaviour of poly(hydroxamic acid) resin prepared from poly(ethylacrylate) towards gold, silver, copper, iron, nickel, cobalt, and zinc in dilute acid solutions was evaluated. Batch method study shows that although this resin shows high affinity towards the gold ion, it can also be used for the extraction of other metal ions. Sorptions of these metal ions by the resin column are complete and their desorptions from the column can be carried out quantitatively by suitable eluants. Further investigations show that gold can be completely separated from nickel, cobalt and zinc in addition to its separations from silver, iron and copper.